Reorientasi Pendekatan Penyuluhan Keluarga Berbasis Dakwah guna Pembentukan Karakter Anak - Rustan (Indonesian Journal of Islamic Counseling, 2023)
Da'wah is an order for every Muslim, including for Islamic religious instructors. Da'wah that targets the formation of children's character requires religious counseling policies that can answer the needs of family groups. The aim is finding the kind forms and rules of family counseling for the formation of children's character through a da'wah approach in the City of Mamuju, West Sulawesi. The research is using a qualitative. Data is collecting through interview and depth observation. There were 6 informants consisting of Islamic religious instructors. Data is analysiing with the Craswell approach. Research reveals that family coaching policies for the formation of children's character are carried out through a da'wah approach by paying attention to the forms of da'wah used by religious instructors based on Surah An-Nahl verse one hundred twenty five consisting of bil-hikmah, bil-Mau'idzah, and bil-Mujadalah. The implications of this are positive and empathetic family counseling models, family counseling inserting honest and patient words, and applying persuasive guidance.